The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1975
DOI: 10.2307/1935308
|View full text |Cite
|
Sign up to set email alerts
|

The Autecology of Sawgrass in the Florida Everglades

Abstract: Investigations were conducted in 1971 and 1972 to characterize typical stands of sawgrass (Cladium jamaicense Crantz) in the southern Everglades. Estimates were obtained of standing crop, plant density, stem length, leaf numbers, growth rate, and nutrient relationships in plant tissue, soil, and water. Measurements were also made of daily rainfall and water depths. These various parameters were estimated monthly over a 12—18 mo period in mature stands, as well as in stands regrowing after wild fires. The matur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
64
0
1

Year Published

1980
1980
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(74 citation statements)
references
References 7 publications
(7 reference statements)
9
64
0
1
Order By: Relevance
“…Within the Transition and Reference zones, highest N (and K) concentrations were associated with periphyton mats and slough-community species, particularly the water lily Nymphaea odorata. Decomposing Nymphaea tissue has been shown to have greater N concentrations than more recalcitrant species like Cladium (Steward and Ornes 1975b;J. Vymazal unpublished data).…”
Section: Vegetation-environment Linkages: Allogenic or Autogenic?mentioning
confidence: 96%
See 1 more Smart Citation
“…Within the Transition and Reference zones, highest N (and K) concentrations were associated with periphyton mats and slough-community species, particularly the water lily Nymphaea odorata. Decomposing Nymphaea tissue has been shown to have greater N concentrations than more recalcitrant species like Cladium (Steward and Ornes 1975b;J. Vymazal unpublished data).…”
Section: Vegetation-environment Linkages: Allogenic or Autogenic?mentioning
confidence: 96%
“…Fire disturbance was expected to play a role in vegetation pattern because Cladium is considered fire tolerant (Steward and Ornes 1975b), and intense fires are believed to be partially responsible for maintaining the sawgrass-slough mosaic (Craighead 1971;Gunderson and Snyder 1994). A composite map of recent, large fires constructed using aerial photographs indicated that more than 50% of WCA-2A had burned at some point during 1981-98 (Florida Game and Freshwater Fish Commission unpublished data).…”
Section: Environmental and Vegetation Variablesmentioning
confidence: 99%
“…The resulting landscape mosaic had small areas of enhanced nutrients or eutrophy in tree islands that were maintained by wading bird nesting, or in local refugia maintained by the cycles of flooding and drydowns that first collected diffuse energy and then concentrated it locally. The remainder of the landscape (sawgrass marshes and wet prairies) adapted to low nutrient thresholds (Steward and Ornes 1975).…”
Section: Surprise Resilience and Flexibilitymentioning
confidence: 99%
“…One of the most publicized perturbations to the system has been excessive inputs of phosphorus (P). The Everglades is a P-limited ecosystem, and its biota are adapted for survival under highly oligotrophic conditions (e.g., Browder 1982, Steward and Ornes 1975a, Steward and Ornes 1975b, Swift and Nicholas 1987, Davis 1991. Indeed, numerous experiments have demonstrated the sensitivity of Everglades biota to P enrichment.…”
Section: Introductionmentioning
confidence: 99%